(untitled) (Veterinary Science, 2020)
In December 2019, an outbreak of a novel zoonotic coronavirus began, called SARS-CoV-2 or COVID-19, which reached pandemic dimensions on March 11, 2020. By March 3, it had already entered República Argentina, while on March 9 the first case occurred in the Province of Rio Negro. In this province, 823 cases were identified with 41 deaths and 602 recovered cases by June 30, giving rise to successive intervention strategies to prevent its arrival in some places without viral circulation, to control outbreaks occurred and, when this objective was achieved, to avoid reintroduction. Among all measures, those related to non-pharmaceutical Interventions or NFI based on Primary Health Care and One Health with integrated participation among health agents of the First Level of Care, veterinary public health and medical areas of the Departments of Activities for the Area and Its Primary Health Care Centers and epidemiology services are a central, highly effective and essential strategy to cut the transmission chain and decreasethe agent’s reproductive capacity (R0) to a value <1. The activities carried out from the appearance of cases were described in the towns of El Bolsón, San Carlos de Bariloche, General Roca and Choele Choel in the Province of Rio Negro during 110 days of the pandemic.